Evaluation of the EMG-force relationship of trunk muscles during whole body tilt - Anders, C.; Brose, G.; Hofmann, G. O.; Scholle, H.-C. (Journal of Biomechanics, 2008)
The study was aimed at the identification of the electromyography (EMG)-force relationship of five different trunk muscles. EMG-force relationships differ depending on changes in firing rate and the concurrent recruitment of motor units, which are linear and S-shaped, respectively. Trunk muscles are viewed as belonging to either the local or global muscle systems. Based on such assumptions, it would be expected that these functionally assigned muscles use different activation strategies.